النسخ في القرآن الكريم بين المثبتين والنافين " دراسة أصولية" - لعجالي, حنـــان (University of Eloued جامعة الوادي, 2017)
إن موضوع النسخ في القرآن الكريم مسألة أصولية عظيمة، وركن عظيم في فهم الأحكام الشرعية، ولأهمية الموضوع ومكانته، كان موضوع دراستي يتعلق بالنسخ في القرآن الكريم بين المثبتين والنافين "دراسة أصولية" تطرقت من خلال هذا العنوان إلى مقدمة ممهدة للموضوع مشتملة على جميع العناصر تقريبا وإلى بيان معنى النسخ عند أهل اللغة والاصطلاح بين المتقدين والمتأخرين، وإلى التعريف بالقرآن الكريم كذلك في اللغة والاصطلاح، كما ذكرت ألفاظ ذات الصلة بالموضوع كالتخصيص، والاستثناء والتقيد، والبَدَاء فكانا هذا المبحث عبارة عن توطئة للدخول في الموضوع. أما في المبحث الأول بعنوان موقف أهل العلم من النسخ مع بيان آرائهم وذكر أدلتهم ومناقشتها ما استطعت إلى ذلك سبيلا فقد كان هذا المبحث لب الدراسة ومربط الفرس. أما المبحث الثاني عن بعض النماذج في دعاوى النسخ في القرآن الكريم فكان هو الجانب التطبيقي لهاته الدراسة اقتصرت فيه على ذكر بعض الآيات المدعي نسخها منها في العبادات (الصلاة، و الصيام)، والسياسة الشرعية، وكذا في الأحوال الشخصية منها عدة المتوفى عنها زوجها، و عقوبة الزنا، وتحريم الخمر. اكتفيت بهذا الحد نظرا لضيق الوقت وتحديد عدد الصفحات المذكرة وذلك خشية أن أتجاوز العدد المطلوب، وفي الأخير تم الخروج بخاتمة تضم أهم النتائج المتوصل إليها، وبعض توصيات. The subject of copying in the Koran is a matter of great fundamentalism, a great corner in understanding the legal rulings, and the importance of the subject and its place, the subject of my study regarding the copies in the Koran between the fixers and the nafin "fundamentalist study" This title includes a comprehensive introduction to the subject, which includes almost all the elements, and to the definition of the meaning of the copies among the people of the language and the term between the adherents and the late, and to the definition of the Holy Quran as well as in the language and the term, as I mentioned the relevant words such as privatization, Is a prelude to entry into the subject. In the first section, entitled the position of the scholars of the copies with a statement of their views and stated their evidence and discussed what you can to this way, it was the subject of study and the link of Persians. The second part of some of the models in the claims of copying in the Holy Quran was the practical aspect of this study. It was limited to mentioning some of the verses that the plaintiff copied from them in the acts of worship (prayer and fasting) and the legitimate policy, The punishment of adultery, and the prohibition of alcohol. I did so because of the lack of time and the number of pages that were mentioned, lest I exceed the required number, and finally came out with a summary of the most important findings, and some recommendations
مذكرة ماستر تخصص اصول فقه
Keywords: : النسخ، القرآن الكريم، المثبتين، النافين، آيات، دعاوى; the Copy, Holy Quran, All Confirmed, Alnavin, Verses, Claims